Homeostatic scaling of neuronal excitability by synaptic modulation of somatic hyperpolarization-activated I(h) channels - van Welie, Ingrid (National Academy of Sciences, 2004)
The hyperpolarization-activated cation current (I(h)) plays an important role in determining membrane potential and firing characteristics of neurons and therefore is a potential target for regulation of intrinsic excitability. Here we show that an increase in AMPA-receptor-dependent synaptic activity induced by α-latrotoxin or glutamate application as well as direct depolarization results in an increase in I(h) recorded from cell-attached patches in hippocampal CA1 pyramidal neurons. This mechanism requires Ca(2+) influx but not increased levels of cAMP. Artificially increasing I(h) by using a dynamic clamp during whole-cell current clamp recordings results in reduced firing rates in response to depolarizing current injections. We conclude that modulation of somatic I(h) represents a previously uncharacterized mechanism of homeostatic plasticity, allowing a neuron to control its excitability in response to changes in synaptic activity on a relatively short-term time scale.